2021
DOI: 10.1111/ahe.12776
|View full text |Cite
|
Sign up to set email alerts
|

Digital information and communication technologies on histology learning: What to expect?—An integrative review

Abstract: The advent of computers and digitized images had a great impact on education in general, but particularly on the morphofunctional sciences that are highly dependent on the intensive use of images (Bloodgood & Ogilvie, 2006). In biomedical education, curricular changes affecting basic science courses have contributed to an increased use of Digital Information and Communication Technologies (DICT). Many educational institutions are faced with such changes, often caused by financial constraints which resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The use of technology also increases the delivery of basic medical sciences courses such as histology, physiology, and anatomy [19,20]. Studies show that applications integrating technology increase academic achievement, histological identification skills, interactive learning, and student satisfaction in histology education [21,22]. In this study, most of the students (81%) stated that the histology course integrated with technological tools would positively affect the quality of education they received.…”
Section: Discussionmentioning
confidence: 67%
“…The use of technology also increases the delivery of basic medical sciences courses such as histology, physiology, and anatomy [19,20]. Studies show that applications integrating technology increase academic achievement, histological identification skills, interactive learning, and student satisfaction in histology education [21,22]. In this study, most of the students (81%) stated that the histology course integrated with technological tools would positively affect the quality of education they received.…”
Section: Discussionmentioning
confidence: 67%
“…Numerous literature reviews and meta-analyses reported the advantages of virtual microscopy before the global wave of digitization from the COVID-19 pandemic in 2019 [12][13][14][15]. Researchers have endlessly highlighted advantages of digital pathology using VM in medical practice [16][17][18][19].…”
Section: Virtual Microscopy and Covid-19mentioning
confidence: 99%
“…Today, technology-supported applications that will facilitate histology education and also provide student-centered learning are applied as a complement to traditional education (Sharmin et al, 2021). Virtual laboratories (Lee et al, 2018), e-learning (Joaquim et al, 2022), digital images (Francis et al, 2022), and various animations and videos are among the alternative education strategies that have emerged in recent years with the developing technology (Campos-Sánchez, 2014). There is a need to develop applications that integrate such innovative approaches in education with traditional methods.…”
Section: Introductionmentioning
confidence: 99%